Pengaruh Thermoterapy terhadap Penurunan Tingkat Nyeri Dada Pasien Infark Miocard Acute di Ruang ICU RSUD Toto Kabila - Zulkifli B Pomalango; Nasrun Pakaya (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Chest pain in patients with acute myocardial infarction is a symptom that arises due to blockage in the coronary arteries which is a serious problem, because it will cause a decrease in cardiac output, so that the blood supply that carries oxygen and nutrients to tissues or cells also decreases. Appropriate use of analgesics or in combination is the most effective management for reducing pain intensity. However, in reality not all pain can be intervened with systemic analgesics. One of the non-pharmacological treatments to reduce chest pain is to use thermotherapy or application of heat to the body to reduce symptoms of acute pain and chronic pain. This study aims to determine the effect of thermotherapy on the pain level of patients with acute myocardial infarction in the ICU room of RSUD Toto Kabila. This study uses a Quasi Experiment One Group Pretest-Posttest Design. The sample used was 30 patients who were determined by Accidental Sampling. Data were collected using a pain level observation sheet and analyzed using the Wilcoxon Rank Test. The results showed that there was an effect of thermotherapy on decreasing the level of chest pain in patients with acute myocardial infarction, before being given thermotherapy the chest pain level with a mean value of 6.40, SD 0.516 and after being given thermotherapy chest pain level with a mean value of 2.40, SD 0.699. The statistical test results obtained the Wilcoxon rank test with a p-value of 0.004 (<α 0.05). It is recommended that thermotherapy be a non-pharmacological action, especially nursing interventions to reduce the level of chest pain in patients with acute myocardial infarction.